Waria dan Pilihan Hidup (Studi tentang Lima Waria di Kota Kendari) - Ashmarita .; Neni Listiana (Laboratorium Jurusan Antropologi, Fakultas Ilmu Budaya, Universitas Halu Oleo, 2015)
This study aims to identify and describe the existence of transvestites in the midst of society and the reason they became transvestites in public Kendari. Data collected by direct observation techniques and in-depth interviews. The data obtained were analyzed by descriptive qualitative. The data analysis is intended to simplify the data obtained so that the younger read and understood. The results showed that, the existence of transvestites amongst the people of Kendari has been widely spreading in the community. Appointment of the existence of transvestites is marked with the number of transgender-transsexuals who cultivate a variety of professions such as transvestites who opened a beauty parlor, working as a singer, activist fighting for the rights of fellow transvestites and not a few of them are working as pimps and prostitutes. Feeling ostracized make-transvestite transsexual is more creative in maintaining life even negative work that was involved in the public eye. A variety of reasons that makes a man choose to be transsexual, among others, have the instinct of womanhood felt since childhood, environmental influences dominated by girls, early experience sex that resulted dependency, trauma such as broken relationship of love between men and women at the age of which resulted in the young man does not believe anymore to women as well as the increasingly harsh demands of life make them choose shortcuts to get the material. The causes of this is what makes a man choose to be transsexual. Keywords: existence, reason, transvestites